TEKNOLOGI PENANGKAPAN BARONANG RAMAH LINGKUNGAN DI KEPULAUAN SERIBU - Darmono, Oktavianto P; Sondita, M Fedi; Martasuganda, Sulaeman (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Fisheries utilization of rabbitfish is one of the big potential resource in Seribu Island. Catch production of rabbitfish in the Thousand Islands has increased, it was influenced by market demand. The impact of continuously rabbitfish exploration is habitat destruction. The aim of research were an inventory fishing gear types for rabbitfish and determine sustainable level of rabbitfish fishing unit. The research method was survey. It was conducted in February-March 2015 and November-December, 2015. Analysis data which used to inventory fishing gear types of rabbitfish in Seribu Islands was descriptive analysis; Sustainable level was analyzed by nine criteria of FAO. The results showed that fishing gear which caught rabbitfish in Seribu Islands were muroami, bamboo traps, wire traps, net traps, surrounding nets, and speargun. Bamboo traps was the most sustainable fishing gear with a score 25.75, based on sustainability levels.